Technical writing - Sebastian, Evelyn L.; Asuncion, Risa P. (MaxCor Publishing House, Inc., 2014)
"This book is further designed to show the different models that can help students write concise and organized document meant for specific readers. These models will familiarized them with the kinds of problems in the workplace which they are going to encounter and to solve. Solving these problems require careful presentation of solutions which are beneficial and workable."--Preface